Peningkatan Kinerja Karyawan Berbasis Talent Management dan Knowledge Management - Masduki; Sopiyan, Pipih (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2021)
Talent management and knowledge management are important forces in improving employee performance. This study aims to determine and prove the effect of talent management and knowledge management on employee performance either partially or simultaneously. The method used in this research is a survey method with associative research type. Population and sample in this research are permanent employees of PT. Sinjaraga Santika Sport Majalengka as many as 88 people. Data was collected through a questionnaire in the form of a list of statements, the method of data analysis used multiple regression analysis. The results of this study indicate that talent management and knowledge management have a positive and significant effect on employee performance either partially or simultaneously.